In Colombia, Mitigate+ looks to work with national stakeholders to achieve low-emissions development - Villarino, Maria Eliza J. (CGIAR System Organization, 2022)
Caquetá represents one of those places that offer great potential for achieving a dual climate change mitigation objective: reducing greenhouse gas emissions and creating carbon sinks. The government and its development partners believe that cocoa production under an agroforestry system allows for the restoration of forest areas, especially those with illicit crops, which were found to be linked to deforestation and conflict in the country. Mitigate+, short for the CGIAR research initiative on low-emission food systems, aims to reduce annual emissions from global food systems by 7% by 2030. It also supports the Colombian government's ambitious pledge on climate change mitigation.